Wykorzystanie leśnych niedrzewnych produktów i turystycznych zasobów lasu na Białorusi - Marozau, Aleh; Kowbasa, Nikolaj (Leśne Prace Badawcze, 2019)
The aim of the research was to review the legal and regulatory framework that controls the use of non-wood forest products and tourism in forests in Belarus and to analyze current information on harvesting of non-wood forest products such as berries, mushrooms, birch sap, honey, medicinal plants, and minor forest resources as well as to study the state of ecotourism in the territory of the forest fund. We demonstrated that the legal base needs to be improved. In particular, the taxes should be redistributed from economic entities involved in collateral forest use to the Ministry of Forestry that manages the forests. Despite the increased anthropogenic impact on understory layers and the adverse global climatic changes of recent decades, the productive capacity of non-wood forest resources in Belarus remains significant. Nevertheless, the resources are not exploited appropriately, although the demand for products in the domestic and foreign markets is consistently high. In this regard, it is necessary to create suitable conditions for stakeholders, including those possessing foreign capital, to participate in economic activity, whilst preserving the coordinating and controlling functions of the Ministry of Forestry as it is the main forest fund holder in the country. Efforts are also being made to develop infrastructure for ecotourism in forests. However, the level of marketing activities aimed at promoting and providing consumers with available tourist products and services does not meet modern requirements.